Low prevalence of non‐alcoholic fatty liver disease in patients with type 1 diabetes is associated with decreased subclinical cardiovascular disease: 在1型糖尿病患者中非酒精性脂肪性肝病的患病率较低与亚临床心血管疾病较少相关. (29th May 2017) - Serra‐Planas, Enric; Aguilera, Eva; Castro, Laura; Rodríguez, Raúl; Salinas, Isabel; Lucas, Anna; Joaquín, Clara; Puig, Rocio; Mauricio, Dídac; Puig‐Domingo, Manel
Abstract: Background: Non‐alcoholic fatty liver disease (NAFLD) has been proposed as an independent cardiovascular risk factor. The present study evaluated the prevalence of NAFLD in a cohort of type 1 diabetic (T1D) patients and its potential relationship with subclinical cardiovascular disease (CVD). Methods: One hundred T1D patients (mean [±SD] age 39.4 ± 7.8 years, disease duration 21.7 ± 8.6 years) were included in the present cross‐sectional study. All subjects underwent abdominal ultrasonography for detection of NAFLD, carotid ultrasonography to measure the carotid intima–media thickness (CIMT) and atheroma plaques, and cardiac tomography for evaluation of the coronary artery calcium score (CACS). Results: Of the study cohort, 12% had NAFLD and 23% had a CACS >0. The T1D subjects with NAFLD had a greater CIMT than those without NAFLD (0.65 ± 0.17 vs 0.55 ± 0.14 mm; P = 0.029), but there were no significant differences between the two groups with regard to CACS, glycemic control, or the presence of carotid plaques. Patients with high liver enzyme concentrations (>20 U/L) had a higher CIMT (0.60 ± 0.16 vs 0.54 ± 0.13; P = 0.04) and there was a higher proportion of altered CACS (17 [73.9%] vs 6 [26.1%]; P = 0.001) and detection of carotid plaques (10 [76.9%] vs 3 [23.1%]; P = 0.014) in this group. Conclusions: A low prevalence of NAFLD was found in the T1D cohort that was associated globally with a low proportion of abnormal CVD imaging markers, although these imaging parameters were worse in subjects in whom NAFLD was detected. Abstract : Highlights Non‐alcoholic fatty liver disease (NAFLD) has been associated with cardiovascular disease. Mediterranean type 1 diabetes (T1D) patients have a low prevalence of NAFLD, and T1D patients exhibit a low prevalence of subclinical atherosclerosis. The present study supports the relationship between NAFLD and subclinical cardiovascular disease even in a Mediterranean area.